STUDI LITERATUR PEMBELAJARAN MICRO TEACHING TERHADAP KETERAMPILAN MENGAJAR MAHASISWA JURUSAN PGSD - Dzil Ikrom, Fadhli; Rahayu, Maulina (Journal of Professional Elementary Education, 2024)
This study aims to examine micro teaching learning on the teaching skills of Elementary School Teacher Education (PGSD) students through a literature study research method. Micro teaching learning is an approach that is widely used in teacher education to improve the teaching skills of prospective teachers through small-scale teaching practices that receive direct feedback. This study analyzes various previous literature and research that focuses on the implementation and outcomes of micro teaching learning in various educational institutions. The results of the study indicate that micro teaching learning significantly improves students' teaching skills, including in the aspects of planning, implementing, and evaluating learning. These findings support the importance of micro teaching as an integral part of the teacher education curriculum to prepare more competent and professional prospective teachers. In addition, this study also identifies several challenges and recommendations for optimizing the implementation of micro teaching learning in higher education environments.